2013
DOI: 10.1002/prp2.2
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of drugs in humanized UDP‐glucuronosyltransferase 1 mice: Similarity with glucuronidation in human liver microsomes

Abstract: Uridine 5′-diphosphate-glucuronosyltransferases (UGTs) are phase II drug-metabolizing enzymes that catalyze glucuronidation of various endogenous and exogenous substrates. Among 19 functional human UGTs, UGT1A family enzymes largely contribute to the metabolism of clinically used drugs. While the UGT1A locus is conserved in mammals such as humans, mice, and rats, species differences in drug glucuronidation have been reported. Recently, humanized UGT1 mice in which the original Ugt1 locus was disrupted and repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Thus, humanized mice offer a better animal model to predict the human drug metabolism and understand the underlying mechanisms. In our recent study, hUGT1 mice showed glucuronidation activity of furosemide, naproxen, imipramine, and trifluoperazine that was comparable to that of humans (Kutsuno et al, 2013). In this study, we investigated the glucuronidation activity of etodolac, diclofenac, and ibuprofen metabolized by UGTs.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, humanized mice offer a better animal model to predict the human drug metabolism and understand the underlying mechanisms. In our recent study, hUGT1 mice showed glucuronidation activity of furosemide, naproxen, imipramine, and trifluoperazine that was comparable to that of humans (Kutsuno et al, 2013). In this study, we investigated the glucuronidation activity of etodolac, diclofenac, and ibuprofen metabolized by UGTs.…”
Section: Discussionmentioning
confidence: 94%
“…After centrifugation at the top speed for 10 min, the supernatant was analyzed by HPLC. Substrate inhibition kinetics were analyzed using a previously reported equation (Kutsuno et al, 2013), where K si is the constant describing the substrate inhibition interaction.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The highly polar glucuronide conjugate generally decreases the bioactivity of the substrate and increases its water solubility, facilitating excretion through bile or urine. Glucuronidation is important in the metabolism of endogenous wastes and a wide range of drugs, including many chemotherapeutics, nonsteroidal anti-inflammatory drugs, and opioids, and in protecting against harmful environmental agents such as bisphenol A (BPA) and benzo-[a]-pyrene (Fang et al, 2002;Hanioka et al, 2008;Kutsuno et al, 2013). Based on evolutionary divergence and homology, mammalian UGTs have been organized into two major families: The UGT1 and UGT2 families.…”
Section: Introductionmentioning
confidence: 99%